2013
DOI: 10.3390/ijms14011428
|View full text |Cite
|
Sign up to set email alerts
|

Buckwheat (Fagopyrum esculentum M.) Sprout Treated with Methyl Jasmonate (MeJA) Improved Anti-Adipogenic Activity Associated with the Oxidative Stress System in 3T3-L1 Adipocytes

Abstract: Buckwheat sprouts contain various bioactive compounds including rutin which have a number of biological activities. We have previously shown that buckwheat sprouts (TBWE) treated with methyl jasmonate (MeJA) significantly increased the amount of phenolics and the antioxidant activity. The aim of this study was to demonstrate the effect of TBWE on anti-adipogenesis and pro-oxidant enzyme in 3T3-L1 adipocytes. We also evaluated the anti-oxidative activity of TBWE in adipocytes by using the nitroblue tetrazolium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…Polygonum aviculare L. ethanol extract exhibits anti-diabetic effect in HF diet-induced obese mice [333]. Buckwheat sprouts exhibits anti-adipogenic and anti-oxidative properties [334].…”
Section: ] and 4-[2-(35-dimethoxyphenyl)vinyl]mentioning
confidence: 99%
“…Polygonum aviculare L. ethanol extract exhibits anti-diabetic effect in HF diet-induced obese mice [333]. Buckwheat sprouts exhibits anti-adipogenic and anti-oxidative properties [334].…”
Section: ] and 4-[2-(35-dimethoxyphenyl)vinyl]mentioning
confidence: 99%
“…MeJA application can enhance total phenolic concentrations in radish, buckwheat sprouts and sweet basil . Several studies have shown that MeJA‐mediated increases in flavonoids or phenolics can enhance antioxidant, antiproliferative and antiadipogenic activities of sweet basil, buckwheat and blackberry . Pérez‐Balibrea et al reported that exogenous application of MeJA increased glucosinolate (GS) concentrations in broccoli sprouts.…”
Section: Introductionmentioning
confidence: 99%
“…and lepidopteran species (Pieris rapae and Trichoplusia ni). MeJA application can enhance total phenolic concentrations in radish, 8 buckwheat sprouts 9 and sweet basil. 10 Several studies have shown that MeJA-mediated increases in flavonoids or phenolics can enhance antioxidant, antiproliferative and antiadipogenic activities of sweet basil, buckwheat and blackberry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, TBWE was strongly inhibited adipogenic transcription factor as well as pro-oxidant enzymes. Methyl jasmonate treatment significantly increased the amount of phenolic compound, resulting in the suppression of adipogenesis and ROS production in the 3T3-L1 cells [74]. The acute effect of consumption of 500 ml of water, water with buckwheat honey, black tea, black tea with sugar, or black tea with buckwheat honey, on serum oxidative reactions was examined in 25 healthy men.…”
Section: Iii-pharmacological Effectsmentioning
confidence: 99%